Continuous use of textured insole improve plantar sensation and stride length of people with Parkinson's disease: A pilot study - Lirani-Silva, Ellen [UNESP]; Vitório, Rodrigo [UNESP]; Barbieri, Fabio Augusto [UNESP]; Orcioli-Silva, Diego [UNESP]; Simieli, Lucas [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (Elsevier, 2017)
Findings involving the acute benefits of textured insoles on gait in people with Parkinson's disease (PD) are still controversial. To our best acknowledge, the continuous use of textured insoles on gait in people with PD has not been investigated yet. The aim of this pilot study was to obtain preliminary data of the effects of textured insoles on gait and plantar sensation in people with PD after one-week intervention and one-week follow-up period. Nineteen patients with PD were distributed into two groups: experimental group and control group. Initially, the plantar sensation was assessed through Semmes-Weinstein Monofilaments. Then, participants performed 5 trials of walking (without insoles) at a self-selected speed. Gait data were collected using an optoelectronic system. Plantar sensation and gait assessments were repeated in three moments: before and after one-week wearing the group-specific insoles, and after one week wearing conventional insoles (follow-up). The textured insole had half-sphere elevations placed in the distal phalanx of the hallux, heads of metatarsophalangeal joints and heel. Results revealed that the use of textured insole for one week improved plantar sensation and stride length. However, only benefits on plantar sensation were maintained after the follow-up period. Our results suggest that the continuous use of textured insoles for one week benefits plantar sensation and gait in patients with PD. These results support the hypothesis that enhanced somatosensory feedback to the sensory system result in an improved motor output of gait.
Keywords: Continuous use; Gait; Parkinson's disease; Plantar sensation; Textured insoles